2021
DOI: 10.4097/kja.21120
|View full text |Cite
|
Sign up to set email alerts
|

The analgesic efficacy of anterior femoral cutaneous nerve block in combination with femoral triangle block in total knee arthroplasty: a randomized controlled trial

Abstract: This article has been accepted for publication and has undergone full peer review but has not beenthrough the copyediting, typesetting, pagination, and proofreading processes, which may lead to differences between this version and the version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Adjunct use of an IPBSN block is associated with significant pain relief after anterior cruciate ligament repair for 16‒24 h [ 18 ]. The addition of anterior femoral cutaneous nerve (AFCN, including the IFCN and MFCN) block to femoral triangle block (FTB) decreases the opioid requirement compared to that of FTB alone after TKA [ 19 ]. These studies indicated that anaesthesia for the superficial tissue of the knee facilitates postoperative analgesia after knee surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Adjunct use of an IPBSN block is associated with significant pain relief after anterior cruciate ligament repair for 16‒24 h [ 18 ]. The addition of anterior femoral cutaneous nerve (AFCN, including the IFCN and MFCN) block to femoral triangle block (FTB) decreases the opioid requirement compared to that of FTB alone after TKA [ 19 ]. These studies indicated that anaesthesia for the superficial tissue of the knee facilitates postoperative analgesia after knee surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies have investigated the effect of a selective block of the MFCN on acute pain after total knee arthroplasty. Kampitak et al showed that a selective block of the anterior femoral cutaneous nerve branches (i.e., an intermediate femoral cutaneous nerve block and MFCN block) combined with a distal femoral triangle block significantly improved acute pain relief after total knee arthroplasty compared to a standalone distal femoral triangle block [ 12 , 13 ]. Furthermore, several clinical studies have compared an injection lateral to the femoral artery at the level where the medial border of the sartorius muscle first covers the femoral artery (i.e., in the proximal femoral triangle) to an injection at the midthigh level midway between the anterior superior iliac spine and the base of the patella (distal femoral triangle block) [ 14 , 15 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the day of the surgery, acetaminophen (650 mg) was administered orally to all patients 30 minutes before surgery as premedication. All surgeries were conducted under spinal anesthesia with 3 mL of 0.5% hyperbaric bupivacaine through a paramedian approach using a 27-gauge, 90-mm spinal needle by a single anesthesiologist (WK) which is an expert regional anesthesiologist with abundant scientific reports about this technique [15][16][17] . If the blockade was insufficient, the patient was excluded.…”
Section: Phase Ii: Clinical Studymentioning
confidence: 99%
“…), which is an expert regional anesthesiologist with abundant scientific reports about this technique. [15][16][17] If the blockade was insufficient, the patient was excluded. All patients received 10 mg of intravenous dexamethasone and 4 mg of ondansetron for postoperative nausea and vomiting prophylaxis.…”
Section: Phase Ii: Clinical Studymentioning
confidence: 99%